THE GREAT EARTH STORMS IN NOVEMBER 1960 AS OBSERVED AT KIRUNA GEOPHYSICAL OBSERVATORY - ORTNER,JOHANNES; EGELAND,ALV; HULTQVIST,BENGT (1961)
The great earth storms caused by the solar flares, which occurred during the period 1020 November 1960, situated at the southern boundary of the auroral zone, are discussed. Possible physical connections between the various parameters recorded by means of a riometer, a VLF receiver, ionospheric sounder equipments, an oblique auroral reflection receiver, magnetometers and cosmic ray telescopes are discussed. Special attention is given to the following features: (1) the good correlation between disturbances of the geomagnetic field and ionospheric absorption of HF radio waves; (2) the world wide cosmic ray increases, the responsible solar proton energies and the extension of the polar cap; (3) unusual propagation conditions for VLF radio waves; (4) absence of auroral echoes at the time, when the strongest geomagnetic activity has been observed; and (5) observation of unusually low daytime reflection heights by means of a 3 Mc vertical ionospheric recorder. (Author)